Digital Presentation of Bulgarian Lexical Heritage. Towards an Electronic Historical Dictionary - Totomanova, Anna Maria (Studia Ceranea, 2012)
The article presents the results of the project “ICT Tools for Historical Linguistic Studies”, funded by the European Social Fund, OP Human Resources. The main project goal was to elaborate electronic tools for creating a Historical Dictionary of Diachronic Type that should present the history of the Bulgarian words from their first written occurrence until today. By the end of the project the team (Faculty of Slavic Studies at Sofia University, Institute for Bulgarian Language, BAS and PAM Publishing Company, Sofia) had at their disposal a set of Old Bulgarian Unicode fonts, meant for publishing medieval texts and a convertor that converts non-Unicode documents into the new standard. The convertor allowed the participants to create in a relatively short time a Diachronic text corpus of Bulgarian medieval texts, containing already more than 90 texts dated from the 10th to the 18th century. The corpus software enables editing the texts and turned out to be an excellent tool for preparing electronic editions of the Old Bulgarian (OCS) manuscripts. In addition to the corpus an electronic dictionary of Old Bulgarian is available, which contains the digitized version of Старобългарски речник, produced by IBL. Both tools are accessible on the project website at the address histdict.uni-sofia.bg. The Standard of the Historical Dictionary took shape during the project course and respective software for elaborating new dictionary entries was designed and tested. The article also displays screenshots that demonstrate the functionalities of both the corpus and dictionary software.